Educational Game Development for Grade VIII Informatics Learning: Pengembangan Permainan Edukatif untuk Pembelajaran Informatika Kelas VIII - Muhammad Aziz Rohmatulloh; Fitria Nur Hasanah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The integration of digital learning media has become increasingly significant in secondary education, particularly in Informatics subjects that require conceptual understanding and logical thinking skills. Specific Background: In Grade VIII Informatics learning, students often experience low engagement and difficulty understanding abstract computational concepts when conventional teaching methods are applied. Knowledge Gap: Although educational games have been widely discussed in instructional media studies, limited research specifically addresses structured game development tailored to Grade VIII Informatics curriculum needs. Aims: This study aims to develop and validate an educational game designed to support Informatics learning for Grade VIII students. Results: The findings indicate that the developed game meets validity criteria based on expert evaluation and receives positive responses from students in terms of usability and learning support. Novelty: The study provides a curriculum-aligned educational game prototype specifically designed for Informatics instruction at the junior secondary level. Implications: The developed media offers an alternative digital learning resource that can support interactive classroom instruction and facilitate student engagement in Informatics learning processes. Keywords: Educational Game, Informatics Learning, Grade VIII Students, Instructional Media Development, Digital Learning Key Findings Highlights: The game prototype fulfilled expert validation standards for instructional use. Student responses demonstrated positive acceptance and practical usability. The media aligns with junior secondary Informatics curriculum structure.